16 Months Follow Up of Patients’ Behavior and Mild COVID-19 Patterns in a Large Cohort of Cancer Patients During the Pandemic - Hajjaji, Nawale; Lepoutre, Kathleen; Lakhdar, Sarra; Bécourt, Stéphanie; Bellier, Charlotte; Kaczmarek, Emilie; Broyelle, Antonin; Giscard, Sandrine; Lartigau, Eric (Frontiers in Oncology, 2022)
Acute severe forms of covid-19 infection are more likely in cancer patients and a growing attention has been given to the persistent symptoms of the disease after severe covid-19. However, mild illness is the dominant clinical presentation of covid-19 infection. To investigate patients' behavior and the short- and longer-term pattern of the disease in cancer patients with mild covid infection, a longitudinal online survey was conducted for 16 months during the pandemic in a large cohort of cancer patients from a French covid-19 hot spot. An online questionnaire was administered at 3 time points between the first wave of the pandemic in France and the fourth wave. 1415 to 2224 patients completed the questionnaires, which queried patients' demographics, their behavior, and covid infection patterns. Results: 70% of the patients were female, 40% had a comorbid condition. More than one third of the participants had breast cancer, and half were survivors. The rate of infection was 30% during wave 1 and 10% at wave 4; most patients had mild covid-19 infection. 25% of infected patients during wave 4 did not seek medical advice. At wave 4, 87% of the patients received at least one dose of vaccine. Systematic compliance to shielding measures decreased over time. The short-term pattern of mild covid changed between wave 1 and wave 4. 22% of infected patients experienced persistent signs for more than 6 months with a negative impact on sleeping, social behavior, and increased consumption of stress-relieving drug. Our results showed a high prevalence of long-lasting symptoms in cancer patients with mild covid-19 infection and inadequate behavior toward the disease and prevention measures among patients.